Bioavailability and metabolism of rosemary infusion polyphenols using Caco‐2 and HepG2 cell model systems. (12th March 2018) - Achour, Mariem; Saguem, Saad; Sarriá, Beatriz; Bravo, Laura; Mateos, Raquel
Abstract: BACKGROUND: Rosmarinus officinalis is an aromatic plant used in folk medicine as a result of the therapeutic properties associated with its phenolic composition, being rich in rosmarinic acid (RA) and caffeic acid (CA). To better understand the bioactivity of these compounds, their absorption and metabolism were assessed in human Caco‐2 and HepG2 cells, as small intestine and liver models, respectively, using RA and CA standards, as well as a rosemary infusion and ferulic acid (FA). RESULTS: Test compounds were partially up‐taken and metabolized by Caco‐2 and HepG2 cells, although a higher metabolization rate was observed after hepatic incubation compared to intestinal incubation. CA was the compound best absorbed followed by RA and FA, showing metabolites percentages of 30.4%, 11.8% and 4.4% in Caco‐2 and 34.3%, 10.3% and 3.2% in HepG2 cells, respectively. RA in the rosemary infusion showed improved bioavailability compared to pure RA. Methyl derivatives were the main metabolites detected for CA and RA after intestinal and hepatic metabolism, followed by methyl‐glucuronidates and glucuronidates. RA was also minimally hydrolyzed into CA, whereas FA only was glucuronidated. Rosemary polyphenols followed the same biotransformation pathways as the standards. In addition, phase II derivatives of luteolin were observed. CONCLUSION: Rosemary polyphenols are partially metabolized in both the intestine and liver. © 2018 Society of Chemical Industry